Development of a bispecific antibody–drug conjugate targeting EpCAM and CLDN3 for the treatment of multiple solid tumors - Meiying Luo; Xiaohuan Wang; Guoji Yu; Jing Ji; Long Li; Fan Song (Experimental Hematology & Oncology)
Abstract Epithelial cell adhesion molecule (EpCAM), a tumor antigen for antibody–drug conjugates (ADCs), is highly expressed in many epithelial cancers. However, the clinical progress of EpCAM ADCs has been challenging, primarily due to their toxicity in normal high-expression tissues such as the gastrointestinal tract. CLDN3 is highly co-expressed with EpCAM in various human malignancies, coupled with its minimal presence in normal tissues, rendering it an ideal target for developing potent therapeutic ADCs. Here, we developed a bispecific ADC (BsADC) targeting EpCAM and CLDN3, designed to avoid toxicity in normal tissues with high EpCAM expression. The parental monoclonal antibodies (mAbs) were screened for high binding and endocytosis activities on tumor cell lines. We then modified them into monovalent structures and selected clones with decreased binding and endocytosis activities. We combined these clones into bispecific antibodies (BsAbs) and finally chose the molecules with restored binding and endocytosis activities as lead molecules. The BsADCs were generated by conjugating the Drutecan (Dxd) to BsAbs via a cleavable linker. These conjugates exhibit potent binding and effectively inhibit the growth of tumor cells with high levels of both EpCAM and CLDN3, indicating their anti-tumor efficacy. Importantly, they show weak binding to cells with high EpCAM but low CLDN3, implying minimal toxicity to normal tissues with elevated EpCAM expression. Moreover, the BsADCs displayed advantageous pharmacokinetics and low toxicity in mice. These findings position the BsADCs targeting EpCAM and CLDN3 as promising candidates for treating multiple solid tumors.